2006
DOI: 10.1017/s1466252307001181
|View full text |Cite
|
Sign up to set email alerts
|

Trace elements and prion diseases: a review of the interactions of copper, manganese and zinc with the prion protein

Abstract: Transmissible spongiform encephalopathies (TSEs) are a family of neurodegenerative diseases characterized by their long incubation periods, progressive neurological changes, and spongiform appearance in the brain. There is much evidence to show that TSEs are caused by an isoform of the normal cellular surface prion protein PrPC. The normal function of PrPC is still unknown, but it exhibits properties of a cupro-protein, capable of binding up to six copper ions. There are two differing views on copper's role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 74 publications
2
29
1
Order By: Relevance
“…There is evidence suggesting that minerals, especially copper, manganese, and zinc, could play a role in the physiopathology of prion diseases (16,17). In contrast with our results, Hopp et al (15) found that feeding of vitamin and mineral supplements was associated with atypical scrapie.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…There is evidence suggesting that minerals, especially copper, manganese, and zinc, could play a role in the physiopathology of prion diseases (16,17). In contrast with our results, Hopp et al (15) found that feeding of vitamin and mineral supplements was associated with atypical scrapie.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast with our results, Hopp et al (15) found that feeding of vitamin and mineral supplements was associated with atypical scrapie. The difference in the association between atypical scrapie and vitamin and mineral supplements in the 2 studies could be explained by differences in local conditions or roles of some minerals (17). Proper balance of minerals is complex because many interactions occur between mineral intake, diet of the animals, and physiologic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found this worthy of mention because scrapie and other prion-related neurodegenerative diseases are also related to Cu homeostasis, in that prions are Cu-binding proteins. The role Cu plays in prion function, however, is not yet clear (Leach et al, 2006).…”
Section: Hippocampal Fe Cu and Zn Regulation In Relation To Gene Exmentioning
confidence: 99%
“…The accumulation of Zn has also been observed following head trauma and epilepsy [59], implying that Zn neurotoxicity may underlie the pathological mechanisms of various injuries. Moreover, the disruption of Zn homeostasis has also been implicated in other neurodegenerative diseases, including AD [60][61][62], prion disease [63], amyotrophic lateral sclerosis [64], and Wilson's disease [65]. Thus, Zn may play a role like that of Janus, the ancient Roman god of doorways who has 2 different faces, in the brain: both Zn depletion and excess Zn cause severe damage to neurons.…”
Section: Carnosine As a Possible Therapeutic Agent For Vasculartype Dmentioning
confidence: 99%